Jamaica Agriculture and LULUCF Inventory needs assessment country profile - Barrios, Julián; Haynes, Connor; Vásquez, Daniela (2025)
The agriculture and land use, land-use change, and forestry (LULUCF) sectors are key determinants of greenhouse gas (GHG) emissions in Latin America and the Caribbean (LAC), both because of their importance in national economies and because of their weight in the climate commitments made under the Paris Agreement. In this context, moving towards more refined methodologies, such as those of Levels 2 and 3 established in the Intergovernmental Panel on Climate Change (IPCC) Guidelines, is essential to improve transparency, reduce uncertainty in national inventories, and support more ambitious and effective mitigation policies. In its first phase, the project “Strengthening national mitigation goals and providing a pathway to reduce emissions across Central and South American agrifood systems” (GIC-LAC) conducted a needs assessment of MRV systems in countries in the region. The analysis was organized into five key dimensions: (i) regulatory and policy framework, (ii) institutional arrangements, (iii) data availability and quality, (iv) governance environment, and (v) stakeholder demand. The methodology used was based on the Level 2 livestock inventory assessment carried out in Africa (Wilkes et al., 2017), ensuring technical consistency and allowing for comparisons between regions. Taken together, the results presented constitute a technical baseline that describes the current state of MRV systems for agriculture and LULUCF in the region. This assessment provides evidence to guide the improvement of national inventories, facilitate the transition to higher-level methodologies, and reduce the uncertainty associated with emissions estimates, thus contributing to the robustness and consistency of reports under the ETF.